Cryopreserved Multipotent Mesenchymal Stromal Cells Restore Fertility in Animals with Chronic Inflammation of Ovaries - Volkova, Nataliya O.; Yukhta, Mariya S.; Stepanyuk, Larisa V.; Chernyshenko, Lyudmila G. (Problems of Cryobiology and Cryomedicine, 2016)
The paper describes the influence of multipotent cryopreserved mesenchymal stromal bone marrow cells under conditions of intravenous administration alone and in combination with ‘Thymalinum’ (immune regulatory peptide complex from cattle thymus) on the fertility of mice with chronic inflammation of ovaries. The animals injected with a physiological saline were assumed as the control. To the day 21 following intravenous injection of cryopreserved multipotent mesenchymal stromal cells alone and in combination with ‘Thymalinum’ to the mice with chronic inflammation of ovaries an increase in a relative number of fertilized ova during superovulation (38 and 33%, respectively) was found, as well as in a pregnancy rate in natural estrous cycle (20 and 23% respectively) and the average litter number (98 and 83%, respectively) compared to the control animals. ‘Thymalinum’ application per se did not affect significantly the studied indices. The difference in body weight between the mice of experimental and control groups was observed only at early terms of observation, and to the day 15 it disappeared. Probl Cryobiol Cryomed 2016; 26(1):84-92.